(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
To keep people healthy, the air they breathe needs to be of high quality. Nearby locations have been found to have high levels of hazardous substances and air pollution. The suggested system measures air quality parameters such IAQI, which is an effective technique to detect poor air quality. System has ESP8266 to link to IOT platform and pass pollution information to the staff. The ability to identify environmental contaminants improves self-care. We’re building an IOT-based pollution monitoring system to track the quality of the air using an internet server as a data source. Monitoring systems currently in use have poor precision and sensitivity, and require lab testing to verify results. As a result, better surveillance systems are required. Because of factors such as industry, urbanisation, population growth, and vehicle use that can harm human health, pollution levels are rising rapidly. In order to monitor the quality of the air, an internet-based web server monitoring system called an IOT-based system is used. It will sound an alert if the air quality deteriorates beyond a specific point, i.e. when dangerous gases such as CO2, smoking, alcohol, benzene, NH3, and NOx are present in substantial quantities in the atmosphere. It will display the air quality in parts per million (PPM) both on the LCD and on the webpage, making it simple to keep tabs on pollution levels.